2018
DOI: 10.1159/000493435
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Organ-Sparing Approach for Locally Advanced Esophageal Cancer

Abstract: Esophagectomy is still the cornerstone of treatment in patients with esophageal cancer. Non-surgical treatment via definitive chemoradiotherapy (dCRT) is currently reserved only for patients not eligible for esophagectomy. Since salvage esophagectomy after dCRT (50-60 Gy) results in increased complications, morbidity and mortality compared to surgery after nCRT (41.4 Gy), the latter seems preferable in the setting of active surveillance. Clinical response evaluations can detect substantial (i.e., tumor regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Active surveillance after nCRT has been proposed for esophageal cancer since high pCR rates are being achieved by current nCRT regimens [5]. The Dutch CROSS trial showed that 5-year overall survival significantly increased from 33 to 47% by applying nCRT consisting of carboplatin and paclitaxel with concurrent 41.4 Gy radiotherapy prior to surgical resection [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active surveillance after nCRT has been proposed for esophageal cancer since high pCR rates are being achieved by current nCRT regimens [5]. The Dutch CROSS trial showed that 5-year overall survival significantly increased from 33 to 47% by applying nCRT consisting of carboplatin and paclitaxel with concurrent 41.4 Gy radiotherapy prior to surgical resection [3].…”
Section: Discussionmentioning
confidence: 99%
“…For these patients surgical resection might not be necessary. Hence, an active surveillance strategy has been proposed in which patients will undergo frequent clinical response evaluations instead of standard esophagectomy [5].…”
Section: Rationalementioning
confidence: 99%
“…Approximately one-third of patients have a pathologic complete response (pCR) after neoadjuvant CRT, which was correlated with significantly improved treatment outcomes [ 2 6 ]. Considering the substantial postoperative morbidity and mortality associated with esophagectomy, as well as the impaired quality of life, an organ-preserving approach with active surveillance could be feasible in patients without residual tumor after neoadjuvant treatment [ 7 ]. In view of the higher radiosensitivity of esophageal squamous cell carcinoma (ESCC) compared with adenocarcinoma, an accurate prediction of pCR prior to surgery is particularly relevant for Asian patients [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those who are at high risk for postoperative complications, but have a high probability of achieving a pCR, could potentially be spared the morbidity and mortality of surgery. The organ-preserving approach with active surveillance is an alternative treatment for these patients 26 28 . Van der Wilk et al reported that patients with esophageal cancer who achieved a clinical complete response after neoCRT and underwent active surveillance had a survival outcome comparable to immediate surgery after neoCRT.…”
Section: Discussionmentioning
confidence: 99%